The use of board games in healthcare teaching - Lickiewicz, Jakub; Hughes, Patricia; Makara-Studzińska, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2020)
Modern healthcare education has occurred in an era of great challenges, but also of great opportunities. Learners have become accus-tomed to being bombarded by multiple stimuli to the point where traditional education often seems boring and monotonous. For this reason, modern teaching methods based on information technology are increasingly being used. Gamification, the use of game elements in a non-entertainment context, is becoming increasingly popular in education. These include board games. The literature on board games highlights many areas in which board games can be effective within healthcare settings. Board games differ from electronic ones primarily because of the element of social interaction, although some electronic games exist in the form of puzzles or competition with the game mechanism itself. The biggest advantages of board games include improving communication and active learning based on interaction with other players. Board games cannot substitute traditional teaching, but they can help students to master particularly difficult concepts. Games help to organise knowledge, engage and motivate students to learn difficult material, but also en-courage students to take responsibility for their learning. Games in medical education, when properly used, can be valuable tools for an instructor. They create a non-threatening environment that supports mutual learning. A properly prepared game, tailored to the subject, allows mastery of the material in less time than in a traditional lecture.